Melting Point Distribution Analysis of Globally Approved and Discontinued Drugs: A Research for Improving the Chance of Success of Drug Design and Discovery. Issue 4 (21st March 2016) - Mao, Fei; Kong, Qingya; Ni, Wei; Xu, Xiang; Ling, Dazheng; Lu, Zhengyu; Li, Jian
Abstract: The melting point (MP), an easily accessible physical parameter, has considerable potential for the judgment of drug‐like properties. However, to the best of our knowledge, there are no useful guidelines for understanding the relationship between the MP and drug‐like properties. To this end, we have constructed the largest MP database (experimental value) of globally approved drugs (3164 organic small‐molecule drugs) and discontinued drugs (417 organic small‐molecule drugs) and subsequently extracted six subdatabases from the whole approved database and two subdatabases from the discontinued database. The MP distribution statistics and analysis of approved drugs reveal five noteworthy observations; moreover, the MP distribution statistics and analysis of discontinued drugs further supplement these criteria. In addition, the comparison of molecular weight (MW) versus MP and Clog  P versus MP distributions of different classes of approved drugs indicated that the MWs and Clog  P values of most drugs in the optimal MP range were not more than 500 and 5, respectively, implying the MP distribution criterion was in accordance with Lipinski's rule of five. Abstract : Mysteries of melting points ! Herein, we report the largest melting point (MP) database (experimental value) of globally approved and discontinued drugs. We subsequently extracted six subdatabases from the "approved" database and two from the "discontinued" database and studied the MP distributions and the relationships of molecular weight versus MP, Clog  P versus MP distributions. We revealed five noteworthy observations, hoping to provide a theoretical foundation for designing new chemical entities with good drug‐like properties.